2022
DOI: 10.1111/jorc.12420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on cognitive impairment in patients undergoing haemodialyses: A systematic review and meta‐analysis of randomised controlled trials

Abstract: Background: The influence of exercise on cognition in patients undergoing haemodialysis has been examined. However, evidence elucidating the effects in this patient group is scarce.Objective: To examine the effect of exercise on cognitive impairment in patients undergoing haemodialysis and provide insight into the effects of various characteristics of exercise on cognitive impairment in this population.Design: A systematic review and meta-analysis, following the guidance of PRISMA was undertaken.Participants: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…A meta-analysis of 42 studies covering 3522 participants found that people treated with HD had worse cognition than the general population, particularly in attention/processing speed and memory [ 53 ]. A recent meta-analysis of randomized controlled trials showed that intradialytic and interdialytic exercise significantly improve cognitive impairment in patients undergoing HD [ 54 ]. Moreover, in a pilot study [ 29 ], cognitive and exercise training performed separately were able to prevent a decline in executive functions and psychomotor speed in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 42 studies covering 3522 participants found that people treated with HD had worse cognition than the general population, particularly in attention/processing speed and memory [ 53 ]. A recent meta-analysis of randomized controlled trials showed that intradialytic and interdialytic exercise significantly improve cognitive impairment in patients undergoing HD [ 54 ]. Moreover, in a pilot study [ 29 ], cognitive and exercise training performed separately were able to prevent a decline in executive functions and psychomotor speed in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The influencing factors of CI in patients undergoing HD were collected and analyzed based on the health ecology model in the study. According to previous publications, 15 influencing factors from five dimensions, including biological indicators, behavioral lifestyles, psychological factors, disease-related problems, and social environmental problems, were collected ( 23 , 24 ). Following the calculation of sample size in the multifactor statistical analysis proposed by Kendall ( 25 ), the recommended sample size is usually 5–10 times the number of variables.…”
Section: Methodsmentioning
confidence: 99%
“…The study reported a significant reduction in the TMT time, indicating a positive effect on cognitive enhancement. Recently, Liu et al [ 90 ] conducted a meta-analysis of these RCTs. The findings indicated that exercise during or between HD sessions significantly improved cognitive function in HD patients.…”
Section: Measures For CI In Patients With Ckdmentioning
confidence: 99%